Environmental and lifestyle risk factors for early-onset dementia: a systematic review: Environmental factors and EOD risk - Bosi, Matteo; Malavolti, Marcella; Garuti, Caterina; Tondelli, Manuela; Marchesi, Cristina; Vinceti, Marco; Filippini, Tommaso (Acta Biomedica Atenei Parmensis, 2022)
Background and aim:The term early-onset dementia (EOD) encompasses several forms of neurodegenerative diseases characterized by symptom onset before 65 years and leading to severe impact on subjects already in working activities, as well as on their family and caregivers. Despite the increasing incidence, the etiology is still unknown, with possible association of environmental factors, although the evidence is still scarce. In this review, we aimed to assess how several environmental and lifestyle factors may be associated with the onset of this disease. Methods: We conducted a literature search in PubMed and EMBASE databases up to May 6, 2022, to retrieve epidemiological studies evaluating the effect of environmental and lifestyle factors on EOD risk. Results: We eventually included 22 studies, ten with cohort and twelve with case-control design. Traumatic injury, especially on the head/brain, some cardiovascular diseases such as atrial fibrillation and stroke, metabolic diseases including diabetes and hypercholesterolemia, and alcohol consumption have been identified as potential risk factors for EOD. Conversely, playing leisure activities including sports (without trauma), higher educational attainment and higher adherence to Mediterranean DASH-Intervention for Neurodegenerative Delay (MIND) diet appeared to be protective for EOD. Conclusions: The literature on environmental risk factors for EOD has been considerably growing in recent years. Overall, it supports an association between some environmental and lifestyle factors with disease risk. However, additional high-quality research is required to confirm these relations and its causal nature (www.actabiomedica.it).